(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Sikhism, as one of the youngest religions in the world, was born in Punjab (India) and Guru Nanak was the founder of Sikh religion. Islam was born as a new faith in Arabia during the 7th Century and Prophet Muhammad was its founder. Guru Nanak realised the suffering of Indian people under the yoke of dual oppression by Brahmanic and Islamic priestly classes on the one hand and the contemporary rulers, on the other. Guru Nanak refers to the state of affairs in his compositions recorded in Sri Guru Granth Sahib (SGGS) as follows “Rajas were ruthless like tigers and the priestly judges were like dogs, and their officials swooped down on people regardless of whether they were sitting or sleeping (i.e., at any time of the day).